LA FIGURA DEL TRADUCTOR EN LAS NORMAS PROCESALES ESPAÑOLAS. ANÁLISIS DE LOS ÓRDENES JURISDICCIONALES CIVIL, PENAL, CONTENCIOSO-ADMINISTRATIVO Y SOCIAL - María de las Heras Caba (Revista Internacional de Doctrina y Jurisprudencia, 2016)
In this article we want to review those Spanish procedural rules with regard to the civil, criminal, administrative and labour jurisdictional orders, which refer to translation issues, in order to identify how the figure of the translator is regulated in the Spanish procedural law.